Migrating Legacy Systems to Service-Oriented Architectures - Matos, Carlos; Heckel, Reiko (Electronic Communications of the EASST, 2009)
This paper presents a methodology for migrating legacy systems towards Service-Oriented Architectures. The approach is based on source code analysis for identifying the contribution of code fragments to architectural elements and graph transformation for architectural migration, allowing for a high degree of automation. In order to transform existing application architectures into SOAs, the methodology has to be used in two dimensions, a technological and functional one. The work presented here is being developed in the context of a collaboration between academia and industry, and is aimed at being applied in real reengineering projects.